Hadith-Sunnah Distinction and Islamic Science Reconstruction: Fazlur Rahman’s Innovative Approach - Rizaka, Maghza; Darwati, Aan; Masruhan, Masruhan; Al-Hakim, Ahmad Hilmy Luqman (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
This research explains Fazlur Rahman’s innovative approach to delineating the distinction between Hadith and Sunnah and its implications for the reconstruction of Islamic science. Rahman identified historical ambiguities in the usage of Hadith and Sunnah within Islamic scholarship, advocating for a clearer differentiation between textual records (Hadith) and the practical applications (Sunnah) of Prophet Muhammad’s teachings. By employing qualitative analysis of primary texts authored by Rahman and supplemented by secondary literature, this study examines Rahman’s nuanced perspectives on these concepts. It critically assesses Rahman’s contributions, emphasizing his endeavor to harmonize traditional Islamic teachings with contemporary scientific paradigms. Rahman’s scholarly approach not only enriches the understanding of Islamic sciences but also underscores the vital integration of Islamic principles with modern knowledge frameworks. His intellectual legacy stands as a crucial link between traditional Islamic scholarship and contemporary critical inquiry, advocating for a nuanced approach that addresses the multifaceted challenges confronting Muslim societies today. Penelitian ini menjelaskan pendekatan inovatif Fazlur Rahman dalam menggambarkan perbedaan antara Hadis dan Sunnah serta implikasinya terhadap rekonstruksi ilmu pengetahuan Islam. Rahman mengidentifikasi ambiguitas historis dalam penggunaan Hadis dan Sunnah dalam kesarjanaan Islam, mengadvokasi pembedaan yang lebih jelas antara catatan tekstual (Hadis) dan aplikasi praktis (Sunnah) ajaran Nabi Muhammad. Dengan menggunakan analisis kualitatif terhadap teks-teks primer yang ditulis oleh Rahman dan dilengkapi dengan literatur sekunder, penelitian ini mengkaji perspektif Rahman yang bernuansa pada konsep-konsep ini. Studi ini secara kritis menilai kontribusi Rahman, menekankan upayanya untuk menyelaraskan ajaran-ajaran Islam tradisional dengan paradigma ilmiah kontemporer. Pendekatan ilmiah Rahman tidak hanya memperkaya pemahaman ilmu-ilmu keislaman, tetapi juga menggarisbawahi pentingnya integrasi prinsip-prinsip Islam dengan kerangka kerja pengetahuan modern. Warisan intelektualnya menjadi penghubung penting antara kesarjanaan Islam tradisional dan penyelidikan kritis kontemporer, mengadvokasi pendekatan bernuansa yang membahas berbagai tantangan yang dihadapi masyarakat Muslim saat ini.